Heterocyclic electrophiles as new MurA inhibitors. Issue 12 (21st November 2018) - Keeley, Aaron; Ábrányi‐Balogh, Péter; Hrast, Martina; Imre, Tímea; Ilaš, Janez; Gobec, Stanislav; Keserű, György M.
Abstract: An electrophilic fragment library of small heterocycles was developed and characterized in the surrogate GSH‐reactivity assay and aqueous stability test that revealed their potential as covalent warheads. Screening the library against MurA from Staphylococcus aureus (MurASA ) and Escherichia coli (MurAEC ) identified heterocyclic fragments with significant inhibitory potency. The validated heterocyclic warhead library might be useful for developing targeted covalent inhibitors for other targets of interest with a new design strategy incorporating heterocyclic electrophiles as warheads. Abstract : An 84‐membered covalent fragment library containing five‐ and six‐membered heterocycles with six different warheads was developed and characterized in a GSH‐reactivity assay and an aqueous stability test. Mapping their reactivity revealed their potential as covalent warheads.